2021
DOI: 10.3390/plants11010066
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Analysis of Essential Oil from Anisosciadium lanatum Boiss.—Chemical Composition, Molecular Docking, and Mitigation of Hepg2 Cancer Cells through Apoptotic Markers

Abstract: Essential oils have been used in various traditional healing systems since ancient times worldwide, due to their diverse biological activities. Several studies have demonstrated their plethora of biological activities—including anti-cancer activity—in a number of cell lines. Anisosciadium lanatum Boiss. is a perennial aromatic herb. Traditionally, it is an edible safe herb with few studies exploring its importance. The current study aims to investigate the chemical composition of essential oil isolated from An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Another study conducted by Shahin et al [ 12 ] reported that the flowers’ EO extracted from Aerva javanica , isolated during four seasons, is considered a good source of natural bioactive antioxidants. Khalil et al [ 13 ] studied the chemical composition of EO isolated from Anisosciadium lanatum and evaluated its anti-cancer potential and mechanistic effect on HepG2 liver cancer cell lines. The obtained results showed that the studied EO was able to regulate the cell proliferation and cell viability in HepG2 liver cancer cells at a sub-lethal dose of 10 to 25 g/mL and displayed reductions in migration and invasion [ 13 ].…”
Section: Bio-pharmaceutical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted by Shahin et al [ 12 ] reported that the flowers’ EO extracted from Aerva javanica , isolated during four seasons, is considered a good source of natural bioactive antioxidants. Khalil et al [ 13 ] studied the chemical composition of EO isolated from Anisosciadium lanatum and evaluated its anti-cancer potential and mechanistic effect on HepG2 liver cancer cell lines. The obtained results showed that the studied EO was able to regulate the cell proliferation and cell viability in HepG2 liver cancer cells at a sub-lethal dose of 10 to 25 g/mL and displayed reductions in migration and invasion [ 13 ].…”
Section: Bio-pharmaceutical Propertiesmentioning
confidence: 99%
“…Khalil et al [ 13 ] studied the chemical composition of EO isolated from Anisosciadium lanatum and evaluated its anti-cancer potential and mechanistic effect on HepG2 liver cancer cell lines. The obtained results showed that the studied EO was able to regulate the cell proliferation and cell viability in HepG2 liver cancer cells at a sub-lethal dose of 10 to 25 g/mL and displayed reductions in migration and invasion [ 13 ]. In addition, the treatment with A. lanatum EO indicated the mitigation of cancer activity by aborting the mRNA of pro-apoptotic markers such as BCL-2,CASPASE-3, CYP-1A1, and NF k B [ 13 ].…”
Section: Bio-pharmaceutical Propertiesmentioning
confidence: 99%
“…The crystal structures of the mice AMPK (PDBID: 5ufu), PI3K (PDB ID: 7r2b) and GULT4 (PDBID: 7wsn) were retrieved from the Protein Data Bank ( ) (accessed on 10 August 2022). Docked ligand–receptor interactions were visualized and analyzed using Discovery Studio 2021 Client trial version, as described earlier by Khalil et al [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…The lysates of cultured cells were prepared using RIPA lysis buffer, then separated on an SDS-PAGE gel and transferred to a PVDF membrane. Western blot assays were performed with the aid of specified primary antibodies: ZEB-2 (mouse monoclonal antibody 1:1500) (Invitrogen, Waltham, MA, USA), PTEN (rabbit polyclonal antibody 1:1000) (Invitrogen, Waltham, MA, USA), iNOS (rabbit polyclonal antibody 1:1000) (Biorbyt, Cambridge, UK), β-actin (rabbit polyclonal antibody 1:2000) (Cell Signaling Technology, Beverly, MA, USA) and its HRP-labeled secondary antibodies [33], followed by detection with an enhanced chemiluminescence reagent. Chemiluminescence of expressed bands were examined to confirm the linear range of the chemiluminescence signals, and the quantifications were performed using the densitometry tool in ImageJ software v1.8.…”
Section: Western Blotmentioning
confidence: 99%